The Influence of Emotional Intelligence and Anxiety on the Academic Success of B.Ed. Students - Kanchan Pandey; Dr. Alok kumar Mishra (Innovative Research Thoughts, 2025)
This study investigates how anxiety and emotional intelligence (EI) both influence students pursuing a bachelor's degree in education (B.Ed.). Although cognitive talents have historically been the key to academic achievement, non-cognitive elements like anxiety and emotional intelligence have become important predictors of student performance. In contrast to anxiety, which can impair learning and concentration and result in worse academic outcomes, emotional intelligence (EI) can improve academic performance by promoting better self-regulation, empathy, and motivation, according to this study's thorough literature review, theoretical discussion, and empirical data. In order to prepare aspiring teachers for holistic professional competence, the paper's conclusion emphasizes the significance of including emotional learning into B.Ed. programs.